Mitofusin-2 acts as biomarker for predicting poor prognosis in hepatitis B virus related hepatocellular carcinoma - Xiumei Wang; Youde Liu; Jing Sun; Wenjing Gong; Ping Sun; Xiangshuo Kong; Miaomiao Yang; Weiwei Zhang (Infectious Agents and Cancer, 2018)
Abstract Objective To investigate the expression of Mitofusin-2 (MFN2) in HCC tissues and its role in the development of HCC. Methods A total of 107 HCC specimens were collected for tissue microarray analysis and immunohistochemistry (IHC) analysis. The relationship between MFN2 expression and clinical features of patients with HCC was analyzed. Results Expression level of MFN2 in HCC tissues was 0.92 ± 0.78, significantly lower than that of matched paracancerous liver tissues (1.25 ± 0.75). Patients with low expression of MFN2 had significantly higher rates of cirrhosis than those with high expression of MFN2 (P = 0.049). Kaplan-Meier survival analysis showed that HCC patients with low expression of MFN2 had a worse prognosis in overall survival than HCC patients with high expression of MFN2 (P = 0.027). Patients with high expression of MFN2 had a better prognosis in disease-free survival compared with HCC patients with low expression of MFN2 (P = 0.047). Vascular invasion and MFN2 expression were shown to be prognostic variables for overall survival in patients with HCC. Multivariate analysis showed that vascular invasion (P < 0.001) and MFN2 expression (P = 0.045) were independent prognostic factors for overall survival. Vascular invasion (P < 0.001) and MFN2 expression (P = 0.042) were independent risk factors associated with disease-free survival. Conclusion Our data revealed that MFN2 expression was decreased in HCC samples. High MFN2 expression was correlated with longer survival times in patients with HCC and served as an independent factor for better outcomes. Our study therefore provides a promising biomarker for the prognostic prediction of HCC and a potential therapeutic target for the disease.